Changes of the Characteristics of the Position of Controller Based on an Analysis of Job Offers in Years 1996-2008 - Dynowska, Joanna; Kes, Zdzisław (Zmiany charakterystyki stanowiska controllera na podstawie analizy ofert pracy w latach 1996-2008, 2010)
The purpose of the conducted research was to analyse controller job offers appearing on the Polish labour market. Thanks to the research the information on the changes in the nomenclature applied for designating the position of controller and as to the tasks comprising controller’s duties within over 10 years was obtained.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 145, s. 32-40
Keywords: job offers; controlling; controller; tasks of a controller